2019
DOI: 10.1111/ics.12531
|View full text |Cite
|
Sign up to set email alerts
|

Photoageing‐related skin changes in different age groups: a clinical evaluation by biophysical and imaging techniques

Abstract: Objectives In view of the lack of studies about the morphological and structural changes caused by solar radiation in young people, the aim of the present study was to evaluate the photoageing‐related changes in the skin of different age groups by biophysical and imaging techniques. Methods Forty‐four healthy female subjects were divided into two age groups: Group 1 (G1): 18–35 years old and Group 2 (G2): 40–60 years old. The skin of malar region of the face was evaluated in terms of mechanical properties, dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 31 publications
(68 reference statements)
3
44
0
Order By: Relevance
“…Other options include LifeViz, 55 standardized before and after photos, and the Skin Colorimeter CL 400 (Courage + Khazaka, Cologne, Germany). 69 …”
Section: Consensus Results/recommendationsmentioning
confidence: 99%
“…Other options include LifeViz, 55 standardized before and after photos, and the Skin Colorimeter CL 400 (Courage + Khazaka, Cologne, Germany). 69 …”
Section: Consensus Results/recommendationsmentioning
confidence: 99%
“…On the other hand, in this study it was not observed the presence of mottled pigmentation in the basal layer for the participants, except for those with melasma. However, another study of our research group that analysed the skin of young women by RCM, it was observed the presence of this pigmentation disorder in the basal layer [7]. In this study, it was observed only a worsening of the pre‐existing skin pigmentary disorders such as melasma or PIHP.…”
Section: Discussionmentioning
confidence: 54%
“…Microscopic images were obtained using the Vivastack imaging system that provides multiple successive depth‐confocal images at a certain site of the tissue, and 3‐by‐3‐μm images were obtained up to a depth of 150 μm. The images were interpreted according to the recent literature to analyse stratum corneum and papillae thickness, honeycomb pattern, presence of vascularization in the spinous layer, pigmentation and structural aspect of papillae and collagen [7,8]. The evaluation was performed in triplicate, and the analysis was positive for the characteristics if at least two stacks revealed an alteration [5,11].…”
Section: Casuistic and Methodsmentioning
confidence: 99%
See 2 more Smart Citations